The Asymmetric and Symmetric Effect of Energy Productivity on Environmental Quality in the Era of Industry 4.0: Empirical Evidence from Portugal - Sowah, James Karmoh, Jr.; Genc, Sema Yilmaz; Castanho, Rui Alexandre; Couto, Gualter; Altuntas, Mehmet; Kirikkaleli, Dervis (MDPI, 2023)
Energy has never been used in the same way or to the extent that it is today. The CO2 level in the atmosphere surpassed the previous record established in 1958 in May 2019 when it hit 415.26 ppm, and the climate system has reached a tipping point. New corporate initiatives are required to create more sustainable eco-market opportunities and enhance stewardship in order to make the transition to net zero carbon emissions. This research investigates the asymmetric and symmetric impact of energy efficiency on environmental quality in Portugal from 1990Q1 to 2020Q4, while accounting for the role of total energy consumption (TEC), trade openness (TRA), and economic growth (GDP) in driving environmental quality in the era of industry 4.0. Portugal has emerged as a crucial player, experiencing rapid economic and financial growth, and attracting an unprecedented inflow of foreign trade. While country growth is appreciable in the monetary sense, this research employs the nonlinear autoregressive distributive lag (NARDL) technique and econometric robustness tests to examine the consequence of CO2 emissions in Portugal. The results verify the asymmetric (different magnitude) impacts across the modeled variables; specifically, a 1% volatility to energy productivity (EP) reduces environmental degradation in Portugal by 3.247606%, while a 1% volatility to GDP, TRA, and TEC increase environmental degradation in Portugal by 0.29119%, 0.717775%, and 0.034088% over the long-term. Energy productivity sources are a great way to help Portugal keep its energy independence and reduce environmental erosion simultaneously. Switching from nonrenewable energy to investing in low-carbon technology is a crucial strategy for decarbonization and the best practical course of policy action for reducing climate change in Portugal.
Keywords: energy productivity; environment; asymmetric; NARDL; symmetric; Portugal; ECONOMIC-GROWTH; CARBON EMISSIONS; CONSUMPTION; REGRESSION; EFFICIENCY; Science & Technology - Other Topics; Environmental Sciences & Ecology